Forecasting electricity loads on national holidays in East Kalimantan. Issue 1 (March 2021) - Hasanah, P; Wiradinata, SA; Azka, M; Sari, CA
Abstract: In the last decades, electricity becomes essential problems in East Kalimantan. Some previous research has conducted to assess the power plant systems and to examine the future electricity demand during the period. Moreover, there are some particular events such as national holidays that bring different impacts on the electricity demand. Forecasting electricity loads on national holidays will give significant information to the stakeholders in order to prevent the power outage of electricity. Two samples of hourly electricity loads in national holidays; New Year and Independence Day during 2015-2018 is analyzed in this research. Furthermore, the SARIMA model is used to estimate the suitable model to predict the future electricity loads. The result shows that SARIMA (2, 2, 0)(0, 1, 0)24 and SARIMA (1, 1, 0)(1, 1, 0)24 are the appropriate model for New Year and Independence Day, respectively. In addition, it is predicted that in 2020 the electricity demand on New Year will rise to 400 MegaWatt based on 95% of confidence intervals. On Independence Day, the electricity consumption will reach 300-450 MegaWatt in 2019 and 2020 with significant growth up to 10% each year.